"After The Fire"; The Legacy of College Dormitory Fire Twenty Years Later. Issue 4 (June 2022) - Conlon, Kathe M.; Dimler, Margaret; Petrone, Sylvia; Marano, Michael
Abstract: In January of 2000 the team at The Burn Center at Saint Barnabas was confronted with what is to date, the single largest burn mass casualty incident since its doors opened in 1977. Looking back through history at other catastrophes shows that, even in the wake of these "landmark events", the lessons learned remain, so that perhaps all was not in vain. 2, 6, 7, 8, 9, 11, 13, 19 While this fire took place more than twenty years ago, its legacy is still being felt today. The following discussion examines some of the key lessons learned, and underscores the fact that positive change does come from tragedy.